PENYULUHAN HAK KESEJAHTERAAN ANAK BAGI ANAK YATIM PIATU SEBAGAI BAGIAN DARI SISTEM EKONOMI ISLAM DI DESA CIBATOK II, KECAMATAN CIBUNGBULANG, KABUPATEN BOGOR - Tri Aditya Putra; Tubagus Rifqy Thantawi; Bayu Purnama Putra (SAHID EMPOWERMENT JOURNAL, 2021)
Abstract Partners in this Community Service activity are santri at the Al Hidayah Islamic Boarding School, whose address is Jl. Kp. Cibinong No.12, Kec. Ciomas, Bogor, West Java. This community service activity starts from June 2021 to July 2021 which begins with an audience, a meeting to discuss themes, signing of collaboration and implementing education / counseling. Pesantren as the oldest education in Indonesia is growing rapidly and is big. Its development is not only textual, but also more up-to-date with the times, with the aim of preparing more advanced students or santri, not only experts in the field of religion, but also on governance, which is also encouraged by holding education in Islamic boarding schools. Protection of children has been regulated in law, namely Law No.23 of 2002 concerning Child Protection (PA). The Law has regulated the rights of children, the implementation of the obligations and responsibilities of parents, family, society, government and the state to provide protection for children. The protection referred to, as stated in article 1 paragraph 2 of the CL Law, "Child protection is all activities to guarantee and protect children and their rights so that they can live, grow, develop and participate, optimally in accordance with human dignity, and protection from violence and discrimination. Orphaned children, as one of the children's social problems, need an established person or institution (orphanage or foundation) as a place to shelter and develop into children who will later lead the country. Orphans are included in the group of children who are still dependent on more established people (Dependent Children). In this case, people or institutions (orphanages or foundations) that have been established play an important role in helping orphaned children meet their daily needs. Due to the majority of orphaned students at the Al Hidayah Islamic Boarding School, Bogor, it is important to carry out this legal education and counseling so that students know and understand about legal protection related to the welfare rights of orphaned children who are cared for in the pesantren environment. The output that will be produced in this activity is a report on the results of community service, We will look for the steps in carrying out these activities, so that the method can be applied in other places with the same problem conditions. Keywords: Children's Rights, Child Protection.